Influences of the processing method and sintering temperature on the translucency of polycrystalline yttria-stabilized tetragonal zirconia for dental applications. Issue 15 (15th October 2018) - Chin, Chuin Hao; Muchtar, Andanastuti; Azhari, Che Husna; Razali, Masfueh; Aboras, Mohamed
Abstract: The achievement of a high esthetic value in polycrystalline yttria-stabilized tetragonal zirconia (Y-TZP)-based dental restorations is hindered by the low translucency of Y-TZP. Thus, this study investigated the effects of processing method and sintering temperature on the translucency of Y-TZP for dental applications. Wet (slip casting) and dry (cold isostatic pressing) processing methods were used. Y-TZP specimens were fabricated by applying the processing methods and sintering at different temperatures (1450–1650 °C). The mechanical, morphological, and optical properties of the Y-TZP specimens were examined and compared. The specimens were benchmarked with a commercial Y-TZP, namely, Cercon © . Results showed that wet processing produced higher mechanical properties and translucency than dry processing. This finding can be mainly attributed to the higher capability of wet processing than dry processing in alleviating the agglomeration in Y-TZP. Among the several specimens that were tested, the slip-casted Y-TZP that was sintered at 1600 °C showed the optimum mechanical properties (99.5% density and 12.7 GPa hardness) and translucency (35% light transmission) for dental applications. Furthermore, the light transmission achieved in this study was approximately three times higher than that of the commercial Y-TZP (13%), thereby indicating a potential alternative to replace the commercial Y-TZP. Highly translucent Y-TZP with excellent mechanical properties was developed in this study through wet processing with a sintering temperature of 1600 °C. The developed Y-TZP can be an alternative to commercial products to produce a highly esthetic dental restoration.